The potential of ion mobility–mass spectrometry for non-targeted metabolomics. (February 2018) - Mairinger, Teresa; Causon, Tim J; Hann, Stephan
Highlights: IM–MS coupled to separation techniques is attractive for non-targeted metabolomics. CCS values are a complementary molecular descriptor for identification workflows. CCS values are conditional and demand for assessment of measurement uncertainty. Abstract : Non-targeted analysis of metabolites in hypothesis-generating workflows has proven its potential to answer essential questions that arise when dealing with complex biological systems. Nevertheless, tracking changes in perturbed systems via accurate quantification and the identification process itself represent the most critical challenges in these workflows. Recent advances in ion mobility–mass spectrometry have enabled this technique to increase the confidence of metabolite annotation by introducing a complementary conditional molecular descriptor, that is collision cross section.